PENYESUAIAN DIRI DALAM BEKERJA PADA PENGASUH DI PANTI ASUHAN CACAT GANDA: STUDI FENOMENOLOGIS - Febriyanti, Dinni Asih; Listiara, Anita; Kahija, Yohanis F. La (Faculty of Psychology, Diponegoro University, 2015)
The study was aimed to describe the work adjustment experience or orphan caregivers in orphanage for multiple disabilities (Panti Asuhan Cacat Ganda/PACG) using qualitative-phenomenology approach. The subjects were three caregivers working in PACG Semarang. Data were collected through semi-structured interview and observation. Data were then transcribed and analyzed to obtain psychological meaning, meaning units, concept map, and subjects’ main experiences. The result shows that orphan caregiver work adjustment is the result of their decision to work at PACG. Work adjustment performed by those orphan caregivers consist of five form of adjustments i.e. the adjustment to caregiving, the adjustment to company’s culture, the adjustment to interact with client, the adjustment to colleagues, and the adjustment to community. Subjects’ work adjustment was influenced by some external and internal factors to build their coping strategies in order to overcome problems that arose during the adjustment. It may be concluded that caregiver’s work adjustment is the synchronization of interpersonal relationship between caregiver and directors, clients, colleagues, and community.